Potret Pertanggung Jawaban dan Pelaporan dan Keuangan Nagari di Kabupaten Pasaman Barat - Henri Agustin; Fefri Indra Arza; Erly Mulyani; Halkadri Fitra (Universitas Negeri Padang, 2017)
This article is a follow up of community service activities conducted by the author team entitled